2016
DOI: 10.3892/ijo.2016.3434
|View full text |Cite
|
Sign up to set email alerts
|

MUC5B silencing reduces chemo-resistance of MCF-7 breast tumor cells and impairs maturation of dendritic cells

Abstract: Abstract. Mucins participate in cancer progression by regulating cell growth, adhesion, signaling, apoptosis or chemo-resistance to drugs. The secreted mucin MUC5B, the major component of the respiratory tract mucus, is aberrantly expressed in breast cancer, where it could constitute a cancer biomarker. In this study we evaluated the role of MUC5B in breast cancer by gene silencing the MUC5B expression with short hairpin RNA on MCF-7 cells. We found that MUC5B-silenced MCF-7 cells have a reduced capacity to gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…This gene could be targeted to slow down tumor growth and metastasis [104]. Moreover, MUC5B silencing was shown to reduce chemo-resistance of breast tumor cells [105], suggesting this as an interesting target also for LUAD, where we found MUC5B as one of the upregulated genes. Mucin expression and its link to chemotherapy resistance has been reported even more broadly in cancer [106].…”
Section: Genes Involved In O-glycosylation Of Mucins Are Differentialmentioning
confidence: 62%
“…This gene could be targeted to slow down tumor growth and metastasis [104]. Moreover, MUC5B silencing was shown to reduce chemo-resistance of breast tumor cells [105], suggesting this as an interesting target also for LUAD, where we found MUC5B as one of the upregulated genes. Mucin expression and its link to chemotherapy resistance has been reported even more broadly in cancer [106].…”
Section: Genes Involved In O-glycosylation Of Mucins Are Differentialmentioning
confidence: 62%
“…A regulatory linkage between dual-specificity phosphatase 28 (DUSP28) and MUC5B/MUC16 was reported in pancreatic cancer cells by a study to elucidate the underlying mechanism by which DUSP28 promotes the development of pancreatic cancer (Lee et al, 2016). The overexpression of the MUC5B gene was reported to lead to the aggressive behavior of breast cancer cells (Valque et al, 2012), and silencing the MUC5B gene efficiently recovered the sensitivity of breast cancer cells to chemotherapeutic drugs by impairing the maturation of dendritic cells and inducing an antitumor immune response (Garcia et al, 2016).…”
Section: Muc5bmentioning
confidence: 99%
“…To understand the effect of abnormal expression of the MUC5B gene on the malignant biological behavior of cancer cells, Lahdaoui et al (2017) knockdown the expression of the MUC5B gene in the human gastric cancer cell line KATO-III and the colon cancer cell line LS174T and found that the downregulation of the MUC5B gene induced a decrease in cell proliferation and migration in vitro and in vivo, partially mediated by the Wnt/β-catenin pathway. In addition, Garcia et al (2016) used short hairpin RNA (shRNA) to knockdown the expression of the MUC5B gene in the breast cancer cell line MCF-7. The results showed that reducing the expression of the MUC5B gene could inhibit the cell adhesion, cell growth and clonogenic ability of MCF-7cells but did not increase apoptosis (Reynolds et al, 2019).…”
Section: Muc5bmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, as well as their direct roles in pathology, some of these Th2-driven outcomes feedback to affect ongoing DC function. For example, the mucin Muc5B has been shown to influence DC maturation in the context of tumour cells [ 69 ], though more work is needed to determine how goblet cell hyperplasia and mucins influence DCs to shape allergic inflammation in the lung.…”
Section: Activation and Induction Of Adaptive Immunity In The Lungmentioning
confidence: 99%